SPOSAB ABP 501 - A SICILIAN PROSPECTIVE OBSERVATIONAL STUDY OF PATIENTS WITH INFLAMMATORY BOWEL DISEASE TREATED WITH ADALIMUMAB BIOSIMILAR ABP 501. (21st January 2021) - Macaluso, Fabio Salvatore; Cappello, Maria; Busacca, Anita; Fries, Walter; Viola, Anna; Costantino, Giuseppe; Magnano, Antonio; Vinci, Elisa; Ferracane, Concetta; Privitera, Antonino Carlo; Piccillo, Giovita; Belluardo, Nunzio; et al.
Abstract: Background and Aims: There are few clinical data on Adalimumab (ADA) biosimilars in inflammatory bowel disease. Methods: SPOSAB ABP 501 is a multicenter, observational, prospective study performed among the cohort of the Sicilian Network for Inflammatory Bowel Disease. All consecutive patients treated with ADA biosimilar ABP 501 from the introduction of the drug in Sicily (February 2019) to February 2020 (12 months) were enrolled to assess its safety and effectiveness. Patients were divided into 3 groups: group A, naïve to ADA and naïve to anti-TNFs; group B, naïve to ADA, previously exposed to anti-TNFs; group C: switched from ADA originator to ABP 501. Results: 559 patients (median age 39 years; CD 88.0%, UC 12.0%) were included, with a follow-up time of 403.4 patient-years. Thirty-six SAEs occurred in 36 patients [(6.4% - incidence rate (IR): 8.9 per 100 person-years (PY)]. The IR of SAEs was higher among patients in group A compared with group C (17.4 vs. 4.8 per 100 PY; IR ratio=3.61; p<0.001) and among patients in group B compared with group C (16.4 vs. 4.8 per 100 PY; IR ratio=3.42; p=0.041). Among ADA-naïve patients (group A+B), 188 (85.8%) had a clinical response after 12 weeks, including 165 (75.3%) who achieved steroid-free remission. Higher treatment persistence estimates were reported for patients in group C compared with group A and B (log-rank p<0.001). Conclusions: Safety and effectiveness of ABP 501 seem to be overall similar to those reported for ADA originator. Switching from originator to ABP 501 was safe and effective.